2014
DOI: 10.1080/10256016.2014.897946
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic investigation of niche partitioning among native carnivores and the non-native coyote (Canis latrans)

Abstract: We employed stable carbon (δ(13)C) and nitrogen (δ(15)N) isotopes within a hypothetico-deductive framework to explore potential resource partitioning among terrestrial mammalian carnivores. Isotope values were acquired using guard hair samples from bobcat (Lynx rufus), coyote (Canis latrans), gray fox (Urocyon cinereoargenteus), and red fox (Vulpes vulpes) in the Adirondack Park, NY, USA. Enrichment along the δ(13)C axis was expected to reflect the use of human sources of food (reflecting a corn subsidy), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 62 publications
1
19
1
Order By: Relevance
“…The range of diet overlap found in this study (0.58-0.75) is at the low end of the range reported by coyote and red fox studies in other North American ecosystems (0.71-0.91), yet these studies either did not take place in areas with resident large carnivore populations (Kitchen et al 1999, Fedriani et al 2000, Neale and Sacks 2001, Kamler et al 2007, Randa et al 2009, Warsen et al 2014, or scant mention of scavenging suggests carrion was not a readily available resource in those ecosystems (Theberge and Wedeles 1989). The effect of wolf abundance on diet overlap between coyotes and foxes in Susitna and Denali, albeit weak, indicates that large carnivore and small prey abundance may jointly influence mesopredator competition through resource partitioning.…”
Section: Discussioncontrasting
confidence: 65%
“…The range of diet overlap found in this study (0.58-0.75) is at the low end of the range reported by coyote and red fox studies in other North American ecosystems (0.71-0.91), yet these studies either did not take place in areas with resident large carnivore populations (Kitchen et al 1999, Fedriani et al 2000, Neale and Sacks 2001, Kamler et al 2007, Randa et al 2009, Warsen et al 2014, or scant mention of scavenging suggests carrion was not a readily available resource in those ecosystems (Theberge and Wedeles 1989). The effect of wolf abundance on diet overlap between coyotes and foxes in Susitna and Denali, albeit weak, indicates that large carnivore and small prey abundance may jointly influence mesopredator competition through resource partitioning.…”
Section: Discussioncontrasting
confidence: 65%
“…Barring two dogs that have coyote-like δ 13 C values (samples 5MT123-03 and 5MT5-01 (Table 6 and Fig 2)), isotopic variation among coyotes is larger than among dogs. This suggests some degree of dietary plasticity with regards to trophic level among coyotes, a finding that is demonstrated in modern ecological studies of coyote as well [45, 46]. Coyotes are able to significantly alter their diet based on food availability and the presence of competitors.…”
Section: Discussionmentioning
confidence: 79%
“…Kurle et al [4] also examined factors driving differences in stable carbon and nitrogen isotope discrimination factors associated with multiple tissues from omnivorous rats held on four diets of comparable protein quality and quantity. Similar to Hobson and Quirk [3], Kurle et al [4] also found that tissue type accounted for some of the variability observed in 13 C and 15 N values. Diet type also controlled differences in discrimination factors.…”
Section: Correction and Discrimination Factors In Mammals Dietmentioning
confidence: 59%
“…Sex may play a role in driving 15 N, but this was likely due to increased growth in males over the course of the study. The authors demonstrate that, when using stable isotopes to investigate mammalian omnivore foraging ecology, it is important to consider that: (a) the sources of dietary carbon affect 13 C, (b) the dietary trophic level at which a mammalian omnivore is foraging affects 15 N, and (c) the 15 N factors associated with tissues with fast isotope turnover rates are not affected by dietary sources.…”
Section: Correction and Discrimination Factors In Mammals Dietmentioning
confidence: 99%